Regional poverty and income inequality in Central and Eastern Europe - Michael Förster; David Jesuit; Timothy Smeeding (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper reports levels of income inequality and poverty in four Central and Eastern European countries: the Czech Republic, Hungary, Poland and Russia. Unlike many previous researchers who examine transition economies, we aggregate the detailed individual-level income surveys made available through the efforts of the Luxembourg Income Study at the regional level of analysis. Although national-level investigations have contributed much to our understanding of the income distribution dynamics, these studies mask intracountry variance in levels of income inequality and thus may not capture the true distribution of household income and accurately reflect individual wellbeing. Accordingly, we compute summary measures of inequality and relative poverty rates, using both local and national relative poverty lines, for the most recent waves of data available.
Keywords: I3; O52; P36; R11; R12; 330; poverty; income inequality; regions; Central and Eastern Europe; Regionale Einkommensverteilung; Armut; Regionale Disparität; Polen; Russland; Tschechische Republik; Ungarn